Tecnologia na escola pública: um olhar sobre o gerenciamento de laboratórios de informática em Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This experience report describes the management of a computer lab during Supervised Internship II, carried out at Almirante Soares Dutra State High School in Santarém, Pará, Brazil. It covers the revitalization of the lab through equipment maintenance, organization of practical classes, and support for teachers in using educational technologies. The main challenges included poor infrastructure, unstable internet connectivity, and lack of technical support, revealing flaws in public policies for socio-digital inclusion. We detail practical actions such as teacher training workshops and pedagogical interventions, and their contributions to teaching and learning processes. The results confirm the transformative potential of technology in education, even in the face of significant adversity. This experience reinforces the need for stronger public policies and strategic investments, especially in the Brazilian Amazon. We conclude that the effectiveness of these government policies depends on both governmental initiatives and the engagement of the school community.
Keywords: Gerenciamento; Laboratórios; Educação; Pública; Tecnologias; Digitais; Políticas; Inclusão; Sociodigital; Públicas; CNPQ::CIÊNCIAS HUMANAS